The Evolving Role of the Cardiac Catheterization Laboratory in the Management of Patients With Out-of-Hospital Cardiac Arrest: A Scientific Statement From the American Heart Association. Issue 12 (19th March 2019) - Yannopoulos, Demetris; Bartos, Jason A.; Aufderheide, Tom P.; Callaway, Clifton W.; Deo, Rajat; Garcia, Santiago; Halperin, Henry R.; Kern, Karl B.; Kudenchuk, Peter J.; Neumar, Robert W.; Raveendran, Ganesh
Abstract : Coronary artery disease is prevalent in different causes of out-of-hospital cardiac arrest (OHCA), especially in individuals presenting with shockable rhythms of ventricular fibrillation/pulseless ventricular tachycardia (VF/pVT). The purpose of this report is to review the known prevalence and potential importance of coronary artery disease in patients with OHCA and to describe the emerging paradigm of treatment with advanced perfusion/reperfusion techniques and their potential benefits on the basis of available evidence. Although randomized clinical trials are planned or ongoing, current scientific evidence rests principally on observational case series with their potential confounding selection bias. Among patients resuscitated from VF/pVT OHCA with ST-segment elevation on their postresuscitation ECG, the prevalence of coronary artery disease has been shown to be 70% to 85%. More than 90% of these patients have had successful percutaneous coronary intervention. Conversely, among patients resuscitated from VF/pVT OHCA without ST-segment elevation on their postresuscitation ECG, the prevalence of coronary artery disease has been shown to be 25% to 50%. For these patients, early access to the cardiac catheterization laboratory is associated with a 10% to 15% absolute higher functionally favorable survival rate compared with more conservative approaches of late or no access to the cardiac catheterization laboratory. In patients with VF/pVT OHCA refractory to standard treatment, a new treatment paradigm is also emerging that uses venoarterial extracorporeal membrane oxygenation to facilitate return of normal perfusion and to support further resuscitation efforts, including coronary angiography and percutaneous coronary intervention. The burden of coronary artery disease is high in this patient population, presumably causative in most patients. The strategy of venoarterial extracorporeal membrane oxygenation, coronary angiography, and percutaneous coronary intervention has resulted in functionally favorable survival rates ranging from 9% to 45% in observational studies in this patient population. Patients with VF/pVT should be considered at the highest severity in the continuum of acute coronary syndromes. These patients have a significant burden of coronary artery disease and acute coronary thrombotic events. Evidence from randomized trials will further define optimal clinical practice.